Effect of Azimuthal Variability in Estimation of HVSR Parameters and Ground Shear Strain at Kota Baru, South Lampung, Indonesia - Ipmawan, Vico Luthfi; Prastowo, Rizqi; Iqbal, Mochamad; Permanasari, Ikah Ning Prasetiowati; Herman, Sofiana (Journal of Science and Applicative Technology, 2025)
Kota Baru, a potential capital of Lampung Province in South Lampung, Indonesia, faces significant earthquake risks due to the Great Sumatran Fault and the Sumatra Megathrust. Geologically, the area is part of the Plio-Pleistocene Lampung Formation, predominantly composed of rhyolite-dacite tuff and volcanoclastic tuff, which can amplify seismic shaking. This study investigates azimuthal variations in the Horizontal-to-Vertical Spectral Ratio (HVSR) across 15 locations in Kota Baru to identify their underlying causes. The results show notable changes in peak amplitude (Ao) and dominant frequency (fo) across different azimuths, with Mean Absolute Deviations (MAD) ranging from 0.96 to 5.71 for Ao and from 0.00 to 1.57 for fo. Maximum HVSR values were predominantly observed at azimuths below 30° across most regions. These variations are likely related to differences in soft layer thickness and/or the presence of a suspected fault near the study area, both of which could influence seismic wave propagation. A model of an 8.9-magnitude megathrust earthquake revealed no significant differences in Ground Shear Strain values, with results remaining within the same Modified Mercalli Intensity (MMI) scale. Therefore, despite azimuthal variability, the assumption of isotropic ambient noise in Kota Baru remains valid.